ENDOCRINE TREATMENT OPTIONS FOR ADVANCED BREAST CANCER — THE ROLE OF FULVESTRANT - J.F.R. Robertson; S.E. Come; S.E. Jones; L. Beex; M. Kaufmann; A. Makris; J.W.R. Nortier; K. Possinger; L.-E. Rutqvist (Опухоли женской репродуктивной системы)
For many years, tamoxifen has been the _gold standard_ amongst anti-oestrogen therapies for breast cancer. However, the selective aro- matase inhibitors (AIs), anastrozole, letrozole and exemestane, have demonstrated advantages over tamoxifen as first-line treatments for advanced disease. Anastrozole is also more effective as an adjuvant treatment in early, operable breast cancer and is being increasingly used in the adjuvant setting. Generally, the selective oestrogen receptor modulators (SERMs), such as toremifene, droloxifene, idoxifene, ralox- ifene, and arzoxifene, show minimal activity in tamoxifen-resistant disease and show no superiority over tamoxifen as first-line treatments. In addition to these agents, other treatment options for advanced disease include high-dose oestrogens and progestins. Response rates for high- dose oestrogens and tamoxifen are similar, but the use of oestrogens is limited by their toxicity profile. Consequently, there is a need for new endocrine treatment options for breast cancer, particularly for use in disease that is resistant to tamoxifen or AIs. Fulvestrant (_Faslodex_) is a new type of steroidal oestrogen receptor (ER) antagonist that downregulates cellular levels of the ER and progesterone receptor and has no agonist activity. This paper reviews the key efficacy and tolerability data for fulvestrant in postmenopausal women in the context of other endocrine therapies and explores the potential role of fulvestrant within the sequencing of endocrine therapies for advanced breast cancer.